Pengaruh kualitas produk, citra merek dan persepsi harga terhadap keputusan pembelian motor chopper di AFR Seniman Custom Bike - Anugrah Putra, Iqro; Vitaharsa, Leonardo Indra (ARKA INSTITUTE, 2022)
In study to determine product quality, brand image and price perception of purchasing decisions using multiple linear regression. The study was conducted by quantitative methods have population in study are AFR Seniman Kustom Bike consumers spread across the Greater Jakarta area. The sampling technique used was non-probability sampling and accidental sampling method. The distribution of this research instrument is 100 respondents and is carried out using a Likert Scale. The analysis is carried out through several stages such as testing classical assumptions (normality, heteroscedasticity, linearity and multicollinearity) using the SPSS version 28 application. Product quality significantly influences purchasing decisions. Meanwhile, brand image has no significant effect on purchasing decisions. And the price perception significantly influences the purchasing decision. So, it can be conclude that simultaneously product quality, brand image and price perception together influence purchasing decisions at AFR Seniman Kustom Bike.